PENGARUH MODAL ORGANISASI BERSIH, PELUANG PERTUMBUHAN, VOLATILITAS LABA, DAN PENJUALAN KREDIT TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Maulida, Rizka; Ikhsan, Adhisyahfitri Evalina (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The aim of this study is to determine the effect of net organizational capital, growth opportunity, earnings volatility, and credit sales either simultaneously or partially toward debt policy. The samples are food and beverage companies listed on the Indonesian Stock Exchange (BEI) during 2011-2014. Purposive sampling method was used to select the data. Total samples are 10 companies with a total of 40 observations for 4 years. The data analysis used is multiple linear analysis by using SPSS version 22.0. The results showed that: (1) simultaneously, net organizational capital, growth opportunity, earnings volatility, and credit sales affect the debt policy; (2) partially, net organizational capital and growth opportunity do not have influence toward debt policy, while earnings volatility and credit sales are positively affect the debt policy.